2018
DOI: 10.1007/s00264-018-4216-0
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral varus osteotomy: results of the lateral open-wedge technique without bone grafting

Abstract: BackgroundThe lateral opening wedge distal femoral osteotomy (LOWDFO) to reconstruct knee alignment in patients with genu valgum originating in the distal femur has gained importance within the last years.PurposeTo analyze clinical and radiographic outcome of patients treated with LOWDFO with respect to bone healing without grafting and patient age.Material and methodsTwenty-two consecutive patients with genu valgum corrected with 23 LOWDFOs using a Tomofix-locking plate were retrospectively analyzed (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…Good functional, clinical, and radiographic outcomes as well as a reported survivorship of almost 90% at 5 years and more than 70% at 10 years have made the LOW distal femoral osteotomy (DFO) an attractive technique for the treatment of symptomatic valgus deformity [ 2 , 3 , 6 , 7 , 17 , 34 ]. Encouraging clinical outcomes are supported by a recently published biomechanical study, which has demonstrated the unloading effect of the lateral compartment after LOW-DFO [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Good functional, clinical, and radiographic outcomes as well as a reported survivorship of almost 90% at 5 years and more than 70% at 10 years have made the LOW distal femoral osteotomy (DFO) an attractive technique for the treatment of symptomatic valgus deformity [ 2 , 3 , 6 , 7 , 17 , 34 ]. Encouraging clinical outcomes are supported by a recently published biomechanical study, which has demonstrated the unloading effect of the lateral compartment after LOW-DFO [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stahelin 26 recommended an oblique osteotomy as it provides large surface area and inherent stability. Majority favour uniplanar osteotomy 2,17,24,27 without increased incidence of nonunion. We prefer uniplanar osteotomy and use an external fixator to control the closure of medial wedge.…”
Section: Single Plane Vs Biplanar Osteotomymentioning
confidence: 99%
“…Für die Patellastabilität ist vor allem eine valgische Beinachse ungünstig. Befindet sich der Ursprung dieser Deformität kniegelenknah, ist sie häufig mit einem verminderten mechanischen lateralen distalen Femurwinkel (mLDFA) verbunden [22]. Aus dieser Überlegung heraus kann eine Indikation zur Beinachsenkorrektur ab ca.…”
Section: Ganzbeinröntgenaufnahmeunclassified